The Influence Day of The Week Effect, Week Four Effect, and Month of The Year Effect toward Stock Return In LQ-45 Index 2015 - 2019 - Ikaputri, Anisa (International Humanities and Applied Science Journal, 2021)
The purpose of this study was to examine the influence day of the week effect, week four effect, and month of the year effect toward stock return in LQ-45 index 2015 – 2019. The data used in this study are secondary data from www.yahoofinance.com. The samples of this study were the company that consistently incorporated in LQ-45 index during the research period in 2015 – 2019. This study used GARCH and t-test models. One of the GARCH models used in this study is IGARCH (Integrated Generalized Autoregressive Conditional Heteroscedasticity). The result of this study indicates the existence of day of the week effect. Specifically, a negative and significant effect on Monday (Monday effect) and positive and significant effect on Tuesday and Wednesday. The week four effect was also found in this study where there was a negative and significant return on Monday 4th week. This study also indicates the month of the year effect were a positive & significant return in January, February, and December, a negative & significant return in September.